Potensi dan Pengaruh Batang Pisang Sebagai Media Filter Pada Pengolahan Air Limbah Pencucian Kendaraan Bermotor - Kusumawardani, Yustika; Subekti, Sri; Soehartono, Soehartono (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2019)
Wastewater vehicle washing that discharged directly into water bodies can increase pollution levels. Wastewater treatment of small-scale vehicle washing businesses must be efficient, no need large areas, easy to operate and economical. The alternative technology is using simple wastewater filtration system. Banana stems can be used for filter media. Previous studies mention banana stems have cellulose content and have high hygroscopic ability. High cellulose content allows the potential to be used as an absorbent media. Hygroscopic properties are useful for absorbing harmful inorganic chemicals. The study was conducted by making a filtration reactor using banana stem filter media with a variation of residence time and filter media thickness. Sample testing by analyzing COD, TSS and Detergent parameters. The test results significant decrease in TSS and detergent parameters. The highest percentage decrease in TSS reached 91% and detergent 96%. COD decreased during the filtration treatment directly, but after that increased with the length of duration. This is due to biological influence and the high percentage of organic matter and biomass of banana stems. It can be concluded that the banana stem potential as a filter media for direct wastewater treatment and effective in reducing TSS and detergents for washing vehicles wastewater.Â